On the motorway safely? (Academic Journal of Internal Affairs, 2021)
The two determinants of transport are safety and speed. Both characteristics are essential for transport processes to be able to meet the demands of society. However, the two aspects have opposite effects, increasing speed could result decreasing road safety, while increasing safety would require speed reduction. Thus, for transport, especially for road transport it is an optimum search process. This process is influenced by many factors, from the average safety level of each vehicle to the state of the infrastructure. From the point of view of countries with a more developed transport culture, the number of road deaths per 1,000 people in Hungary is high. At the same time, there are societies from which Hungarian transport morale and road safety are high. As we can see the real safety of a transport system that is considered safe by the society also depends on the internal expectations of it. Increasing the road safety levels is a fundamental task, which requires the exploration of the actual problems. In this paper we examine the question of the role of the Hungarian high speed road infrastructure from the traffic safety’s point of view.
Keywords: highway; motorway; road traffic; accident